PELAKSANAAN PENDIDIKAN INKLUSI DITINJAU DARI FUNGSI MANAJEMEN DI SD NEGERI 40 DAN SD NEGERI 117 PEKANBARU - Deti Desmita; Zulfan Saam; Hasnah Faizah AR (Universitas Riau, 2021)
This research aims to analyze the implementation of inclusive education which investigate through management function in public primary school 40 and public primary school 117 Pekanbaru. Informant which interviewed in this research were the school principal, coordinator of inclusive education, teacher and student guardian. While the instrument used in this study were observation, interview, and documentation. Data analysis used to describe the implementation of inclusive education in primary public school 40 and 117 Pekanbaru. The result of this research shown that the implementation of inclusive education has been going well. The implementation of inclusive education focuses on planning, organizing, actuating and controling the implementation of inclusive education. This research describe that inclusive education management believed to be able to contribute on education quality in public primary school 40 and 117 Pekanbaru.